Pengaruh Bagi Hasil, Promosi, dan Kualitas Pelayanan terhadap Keputusan Nasabah Bertransaksi Simpanan Akad Mudharabah di Bprs Pamekasan - Rahman, Fadali; Fajar, Achmarul; Efendi, Junaidi; Kunaifi, Aang; Fajar, Ainul (Al-Maqashid: Journal of Economics and Islamic Business, 2025)
This study aims to analyze the effect of profit sharing, promotion, and service quality on members' decisions in making mudharabah savings transactions at BPRS Pamekasan. Using a quantitative approach, this study involved 100 respondents from a total population of 3,711 customers, selected through the Slovin formula and incidental sampling techniques. Data analysis was carried out using multiple linear regression to determine the factors that influence customers' decisions in choosing mudharabah savings products. Based on the results of the partial test (t-test), the profit sharing variable showed a t-value of 2.354 which was greater than the t-table of 1.660. This shows that the profit sharing variable has a significant effect on members' decisions in making savings transactions with mudharabah contracts at BPRS Pamekasan. Furthermore, the promotion variable obtained a t-value of 2.415> t-table 1.660, which also shows a significant effect on members' decisions to make transactions. This indicates that the promotional strategy carried out by the bank can influence customer preferences in choosing savings products based on mudharabah contracts. Meanwhile, the service quality variable shows a t-value of 2.393, which is also greater than the t-table of 1.660. These results indicate that service quality has a significant influence on members' decisions in making mudharabah savings transactions. The results of the simultaneous test (F-test) show that the F-value of 7.263 is greater than the F-table of 2.70. This means that simultaneously, the profit sharing, promotion, and service quality variables have a significant influence on members' decisions in making savings transactions with mudharabah contracts at BPRS Pamekasan. This finding shows that the success of Islamic financial institutions in attracting customers' interest in savings products does not only depend on the amount of profit sharing, but also on the effectiveness of the promotion and the quality of service provided. These three factors simultaneously form positive customer perceptions of Islamic savings products